2023
DOI: 10.1002/adsu.202300077
|View full text |Cite
|
Sign up to set email alerts
|

Why Membranes Matter: Ion Exchange Membranes in Holistic Process Optimization of Electrochemical CO2 Reduction

Abstract: Reducing carbon dioxide to value‐added chemicals by electrolysis is a promising strategy to substitute fossil‐based processes. Research on CO2 electrolysis has vastly progressed, focusing on catalysis and electrode design, leaving an essential question on the central part of the electrolyzer: Which type of ion exchange membrane is best suited for CO2 electrolysis from an economic perspective? To address this question, holistic process optimization of CO2 reduction and product purification is applied. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 97 publications
(250 reference statements)
0
7
0
Order By: Relevance
“…To find this optimum, several studies investigated the separation cost and concluded that the single‐pass conversion should only be optimized, if the cell voltage increase stays below 0.2 V and the CO Faradaic efficiency does not decrease significantly. [ 1,35 ] Hence, for our cell the 5 mL min −1 flow rate might be the optimum with a FE CO close to 90% and a single‐pass conversion of 49%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To find this optimum, several studies investigated the separation cost and concluded that the single‐pass conversion should only be optimized, if the cell voltage increase stays below 0.2 V and the CO Faradaic efficiency does not decrease significantly. [ 1,35 ] Hence, for our cell the 5 mL min −1 flow rate might be the optimum with a FE CO close to 90% and a single‐pass conversion of 49%.…”
Section: Resultsmentioning
confidence: 99%
“…From a techno‐economic point of view, carbon monoxide (CO), ethylene, and formic acid are seen as most viable products. [ 1–3 ] Electrolyzers for the electrochemical reduction of CO 2 to CO are the most mature technology compared to other products, showing high product selectivity above 90% and partial current densities for CO of more than 1 A cm −2 . [ 4–7 ] However, the ideal electrolysis cell design is still under debate with several different cell architectures currently being investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lifetime of an electrolysis cell configuration is a crucial factor when evaluating the feasibility of using electrolysis technology for industrial applications. Several key components of the cell, including the electrodes, membrane type, and other materials, influence its longevity and economic viability. Rumayor and co-workers conducted a significant techno-economic study focused on the electroconversion of carbon dioxide (CO 2 ) into formate, a process that carries substantial implications for sustainable energy and environmental management. Their research delves into comparing this innovative electroconversion approach to the conventional method of formate production, which involves the hydrolysis of methyl formate.…”
Section: Future Outlook: a Perspectivementioning
confidence: 99%